SIMULATION OF A QUAY WALL FOUNDATION ON AN IMPROVED SEABED. THE EXAMPLE OF THE NEW PORT OF PATRAS - Botsou, I.; Botsou, M.; Loupasakis, C. (Bulletin of the Geological Society of Greece, 2016)
The current study examines the possibility of simulating a quay wall foundation on a gravel pile improved seabed by using the finite element method. For this purpose data from the construction of the New Port of Patras were used. The behavior of the construction was simulated by conducting a series of parametric analyses altering the length and the density of the gravel piles as well as the gradient and the volume of the preloading embankment. Important conclusions regarding the safety factor and the deformations rate of the construction were finally extracted. The simulations were conducted by using PLAXIS 2D.